2012
DOI: 10.4085/1062-6050-47.5.15
|View full text |Cite
|
Sign up to set email alerts
|

Kinesio Taping and the Circulation and Endurance Ratio of the Gastrocnemius Muscle

Abstract: Context: Kinesio Tex tape is a therapeutic tape that is applied with the Kinesio-taping (KT) method and is theorized to increase circulation and subsequently improve muscle function. However, little research has been conducted to determine how KT affects performance.Objective: To determine the effect of KT on muscular endurance ratio, blood flow, circumference, and volume of the gastrocnemius muscle.Design Intervention(s): Tape was applied based on group assignment. The treatment KT group received the ankle-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 29 publications
(46 reference statements)
4
43
3
2
Order By: Relevance
“…Another study also suggested that fatigue seems to have an effect on active joint reposition sense 16) . As a result from muscle fatigue, muscle spindle information became 25 ) , delayed onset muscle soreness (DOMS) 26 ) and flexibility 27) . However, various literature has provided contradictory findings of the benefits of KT 28,29) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also suggested that fatigue seems to have an effect on active joint reposition sense 16) . As a result from muscle fatigue, muscle spindle information became 25 ) , delayed onset muscle soreness (DOMS) 26 ) and flexibility 27) . However, various literature has provided contradictory findings of the benefits of KT 28,29) .…”
mentioning
confidence: 99%
“…KT was invented in Japan, in the 1970s by Dr. Kenso Kase 17 ) . Over the past years, numerous studies have attempted to explain the therapeutic effect of KT on muscle strength [17][18][19] , balance 20 ) , proprioception 21 ) , range of motion (ROM) 22) , pain 23) , movement kinematic 24) , blood circulation 25 ) , delayed onset muscle soreness (DOMS) 26 ) and flexibility 27) . However, various literature has provided contradictory findings of the benefits of KT 28,29) .…”
mentioning
confidence: 99%
“…(9) Quando avaliado o desempenho, uma pesquisa com 61 participantes, foi avaliado que os efeito do KT sobre a resistência, o fluxo de sangue, a circunferência, e o volume do músculo gastrocnê-mio, onde observaram não houve melhora na função anaeróbica e também não afetou a circulação do músculo. (15) Quanto à força muscular um estudo com 14 padelistas não registrou diferença estatisticamente significativa no que se refere à força isométrica máxima de preensão manual após a utilização do KT. (16) Porém, um artigo semelhante com 21 atletas colegiais avaliou os efeitos imediatos do KT na força do antebraço onde se concluiu que pareceu haver um aumento na sensação de força dos mús-culos do antebraço imediatamente após aplicação.…”
Section: Discussionunclassified
“…Bantlama için %96 pamuk, %4 likradan oluşan, suya dayanıklı, gözenekli ve adhezif yapıda, 5 cm eninde ve 0.5 mm kalınlığında bant (Nasara® Original Kinesiology Tape, Kore) kullanıldı. Tüm bantlamalar, KT uygulama eğitimi almış hekim tarafından "calf" bölgesini kapsayacak şekilde gerçekleştirildi (10).…”
unclassified